Droplet characteristics in monsoon clouds before rain as observed over a high altitude site in Western Ghats, India. (15th September 2021) - Leena, P.P.; Varghese, Mercy; Anil kumar, V.; Basheer, Anas Ibnu; Pandithurai, G.
Abstract: The cloud droplet size distribution (CDSD) and microphysical properties prior to monsoon rain events is studied using in-situ ground observations over a high altitude site in Western Ghats, India. The cloud microphysical properties, such as cloud droplet number concentration (CDNC), liquid water content (LWC), cloud droplet spectrum, droplet effective diameter (ED), droplet mean radius (Rm ), spectral width (σ), and relative dispersion (ε) showed a considerable variation. A detailed analysis of CDSD before rain events showed single and multi-mode patterns which varied from case to case. An apparent variation in cloud microphysical properties is noted for both single and multi-mode cases. Large cloud droplets were found in both single and multi-mode clouds, and analysis revealed the possibility of entrainment of aerosols into these clouds leading to multi modes in the CDSD. Observed rain event duration indirectly suggested higher warm rain depths (D*) when multi-mode cases are observed. Highlights: Cloud droplet characteristics before monsoon rain event is studied using in-situ ground observations. Single and Multi-modeal cloud drop size spectra observed before rain events. CDNC, LWC, ED, Rm,  σ and ε, analyzed for single and multi-mode showed distinct variation. Entrainment of aerosols from the cloud base probable cause of multi modes in the CDSD.